Supporting Global Communications of 6G Networks Using AI, Digital Twin, Hybrid and Integrated Networks, and Cloud: Features, Challenges, and Recommendations - Shaymaa Ayad Mohammed; Sallar S. Murad; Havot J. Albeyboni; Mohammad Dehghani Soltani; Reham A. Ahmed; Rozin Badeel; Ping Chen (Telecom, 2025)
The commercial deployment of fifth generation (5G) mobile communication networks has begun, bringing with it novel offerings, improved user activities, and a variety of opportunities for different types of organizations. However, there still exist several challenges to implementing 5G technology. Sixth generation (6G) wireless communication technology development has begun on a worldwide scale in response to these challenges. Even though there have been many discussions on this topic in the past, many questions remain unanswered in the present literature. The article provides a comprehensive overview of 6G, including the common understanding of the concept, as well as its technical requirements and potential applications. A comprehensive analysis of the 6G network design, potential uses, and key elements are covered. This research article delineates future study topics and unresolved challenges to stimulate an ongoing global discourse. This analysis and content of this study supports the use of different applications and services that will benefit the community in the near future using the 6G technology. Subsequently, recommendations for each problem are provided, offering solutions to unresolved difficulties where functionalities are anticipated to improve, hence enhancing the overall user experience.